2021
DOI: 10.1177/0022034520983808
|View full text |Cite
|
Sign up to set email alerts
|

Oral Organoids: Progress and Challenges

Abstract: Oral organoids are complex 3-dimensional structures that develop from stem cells or organ-specific progenitors through a process of self-organization and re-create architectures and functionalities similar to in vivo organs and tissues in the oral and maxillofacial region. Recently, striking advancements have been made in the construction and application of oral organoids of the tooth, salivary gland, and tongue. Dental epithelial and mesenchymal cells isolated from tooth germs or derived from pluripotent stem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 43 publications
0
29
0
Order By: Relevance
“…Such approach may be superior (both material- and function-wise) to the traditional, still suboptimal synthetic implants, among others suffering from lack of physiological functionality, inferior bone integration and absence of innervation. Embryonically derived, bioengineered mouse tooth germs have been shown capable of forming a functional tooth unit after transplantation in an emptied dental cavity of the mouse [ 18 , 20 ]. Our organoid and assembloid models may provide essential puzzle pieces toward developing human tooth germs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such approach may be superior (both material- and function-wise) to the traditional, still suboptimal synthetic implants, among others suffering from lack of physiological functionality, inferior bone integration and absence of innervation. Embryonically derived, bioengineered mouse tooth germs have been shown capable of forming a functional tooth unit after transplantation in an emptied dental cavity of the mouse [ 18 , 20 ]. Our organoid and assembloid models may provide essential puzzle pieces toward developing human tooth germs.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, epithelial organoid models are established without the need for prior isolation of the epithelial (stem) cells from the dissociated whole-tissue sample since the accompanying mesenchymal cells do not thrive in the specific culture conditions used and are swiftly lost at culture and passaging [ 13 , 14 , 16 , 17 ]. Although meanwhile derived from numerous organs, epithelial organoids have not been established yet from human tooth [ 18 , 19 ]. A previous study reported that ERM cells, seeded in Matrigel, grew as ‘organoids’ [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Organoids have been established for the salivary gland, lingual epithelium, and taste buds and show similar characteristics to those of the corresponding organs [ 124 ]. Salivary gland organoids can be obtained with two methodologies.…”
Section: Overview Of Different Types Of Dental Stem Cellsmentioning
confidence: 99%
“…Organoid-based reconstruction strategies have emerged as a potential 3DA for reconstructing dental tissues. These strategies involve the replication of the spatial-temporal cell interactions via co-culture or the compartmentalization of dental epithelial and mesenchymal cells digested from tooth germs within scaffolds followed by the organoid culture within a bioreactor or in vivo transplantation (Gao et al, 2021). Vascular endothelial cells have been incorporated into the system to develop vascularized tooth germ organoids (Smith et al, 2017).…”
Section: Novel 3d Approaches For Tissue Engineering Applicationsmentioning
confidence: 99%